Developments in natural intelligence research and knowledge engineering : advancing applications - Wang, Yingxu (Information Science Reference, 2012)
"This book covers the intricate worlds of thought, comprehension, intelligence, and knowledge through the scientific field of Cognitive Science, covering topics that have been pivotal at major conferences covering Cognitive Science"--Provided by publisher.